Analisis Kesalahan Penggunaan Possessivpronomen dalam Kalimat Sederhana Bahasa Jerman - Saud, Syukur; De Ornay, Hendrik Paschaliano; Al-Ilmullah, Syarifah Fathimah (Academic : Journal of Social and Educational Studies, 2024)
Abstract. This study aims to identify the types of mistakes made by students when using possessive pronouns. The researcher conducted a descriptive qualitative research, selecting a sample of 36 students from class XI IPA 7 SMAN 12 Makassar using random sampling technique. The research instrument used was a test, and a total of 407 errors were found. Among these errors, 153 were related to the use of possessive pronouns in the nominative case, categorized as high (37.59%), while 254 errors were found in the accusative case, categorized as very high (62.41%). Overall, the total error rate in the use of possessive pronouns in simple German sentences by the students was 56.52%. Therefore, it can be concluded that the level of errors in the use of possessive pronouns in simple German sentences by the students of class XI IPA 7 SMAN 12 Makassar is considered to be very high.Keywords: Error analysis, Possessivpronomen, German.